AN EXPLORATORY STUDY ON STUDENTS’ ANXIETY IN THE PROCESS OF COMPOSING AN ENGLISH ESSAY - Diana Achmad; Muhammad Aulia; Roni Ageng Hidayatullah; Yunisrina Qismullah Yusuf (English Review: Journal of English Education, 2023)
Writing proficiency is a crucial language skill for students to acquire, necessitating the production of compositions such as essays. This research aims to identify the manifestations of anxiety experienced by students during the composition of English essays and to ascertain the underlying factors precipitating such apprehension. Participants consisted of 34 fifth-semester students from the Department of English Education at Universitas Syiah Kuala. Employing qualitative methodology, the study utilized questionnaires and interviews as research instruments to collect data. Questionnaires were used to capture data concerning diverse forms of student anxiety, while interviews were conducted to elucidate the determinants of anxiety specifically related to composing English essays. Outcomes revealed that cognitive anxiety was predominant, afflicting 43.5% of fifth-semester students, showcasing its prevalence in this cohort. Additionally, language complexities, self-confidence deficits, fear of critical evaluation, and the pursuit of perfection emerged as pivotal sources of essay-writing apprehension. These findings underline the multifaceted nature of student anxiety during English essay composition, thereby serving as a valuable resource for educational stakeholders seeking insights to enhance students' writing competencies.